Synthesis, characterization and excellent antibacterial property of cellulose acetate reverse osmosis membrane via a two-step reaction. (15th July 2019) - Li, Fu; Fei, Pengfei; Cheng, Bowen; Meng, Jianqiang; Liao, Liang
Highlights: Cellulose acetate RO membrane was bi-antibacterial modified under mild condition. Bromoacetyl bromide and tertiary amine were introduced in turn. Modifying affected membranes hydrophilic, electronegative and mechanical property. N, N- dimethyloctylamine modifying led to the best comprehensive membrane performance. Bactericidal rates of broad-spectrum antibacterial RO membrane were higher than 99.9%. Abstract: In order to improve the antibacterial efficiency and spectrum of cellulose acetate reverse osmosis membrane (CA–RO), both quaternary ammonium and bromoacetyl groups were introduced into cellulose diacetate under mild conditions forming CA–RO with bi-antibacterial groups for seawater desalination. Bromoacetyl bromide and a series of tertiary amine were chosen as the modification agents respectively. The characterization results showed that both two antibacterial groups were successfully introduced with a certain density. The obtaining membrane had a less hydrophilic but more electronegative surface as well as improved mechanical property. The flux values increased firstly and decreased subsequently after twice modifications while the salt rejection rose. The membrane modified with N, N- dimethyloctylamine (DMOA) had the optimal comprehensive performance of flux and salt rejection. The antibacterial testing results indicated that the resulting RO membranes showed high antibacterial efficiency and broad-spectrum. Their bactericidal rates against gram-negative Escherichia coli ( E. coli ) and gram-positive Staphylococcus aureus ( S. aureus ) were more than 99.9%.